A BIM-based Detailed Electrical Load Estimation, Costing and Code Checking - Jasim Farooq; Paawan Sharma; Sreerama Kumar R (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Building Information Modeling (BIM) has established into a powerful solution for our construction requirements throughout its life cycle. Compared to conventional methods, BIM offers simple, faster and accurate methodology for modelling, estimation and analysis. In this paper, a novel Autodesk Revit add-in tool named as “Electrical System Estimation and Costing Tool”(ESECT) is proposed for the simultaneous estimation of electrical connected load, demand load, Volt Ampere per square meter, cost of electrical system construction and monthly bill from a residential building model and the add-in tool is developed by using Visual basic C# language.  Research results indicate that wide range of BIM automated tools are possible for code-checking and estimation for design analysis at all stages of electrical system development and eventually leads to better design and cost reduction.